“Mother first, student second”: challenging adversity and balancing identity in the pursuit of university-level education as First Nations mothers in Northeastern Ontario - Rowe, Robyn (Laurentian University of Sudbury, 2017)
The literature surrounding the educational experiences of Indigenous Peoples is an ever-growing and diverse area of research in Canada. However, within this field, the voices of First Nations mothers attending post-secondary needs further development. Through a decolonizing methodology and the use of autoethnography and Indigenous storytelling, this project was designed to explore and better understand our experiences as First Nations student-mothers during the pursuit of university-level education while caring for our children. I argue that Canada’s oppressive history of colonialism and the resulting intergenerational trauma have had specific implications on the post-secondary experiences of the First Nations mothers who participated in this research. The First Nations student- mothers from Laurentian University in Sudbury, Ontario, Canada who contributed to this research tell diverse stories about their experiences however, our narratives intersect in several ways. Areas of interest that emerged from the collected narratives include: (1) how we, as First Nations student-mothers have overcome obstacles, including what difficulties arose for us in the decision to pursue post-secondary education; what motivators contribute to our ongoing success, and how we experience self-doubt and internalized oppression despite our achievements and (2) how we, as First Nations student-mothers have blended our identities as First Nations women, mothers, and students within the university experience. Ultimately, this project aimed to contribute to continued efforts towards decolonization while furthering Indigenous-led research which hopes to improve the educational outlook for future generations of First Nations mothers. Masters (MIR) of Indigenous Relations